The Metis aboriginal rights revolution - Stevenson, Mark L. (Allard Research Commons, 2009)
When the Metis were included in section 35 of the Constitution Act 1982, Metis leaders were euphoric. With the constitutional recognition of the Metis as on of the three Aboriginal peoples of Canada and the protection of Metis Aboriginal rights in section 35 of the Constitution Act, 1982, it was thought that the battle for recognition was over. Surely the next step would be the federal government's recognition of its jurisdiction for the Metis and the recognition by the courts and the Crown that Metis have Aboriginal rights that can be exercised along with those of the Indians and the Inuit. But Metis expectations were short lived. More than twenty years later, Canada refuses to recognize it has legislative jurisdiction for the Metis, arguing that Metis are a provincial legislative responsibility. And both the federal and provincial governments have failed to conduct themselves in keeping with the principle of the "honour of the Crown" because they consistently deny that Metis have Aboriginal rights. Whenever Metis harvesters attempt to exercise their rights, the Crown is there as a game warden, prosecutor or jailor, but never as a fiduciary to maintain the Crown's honour. The Crown often argues that without a clear understanding of Metis definition and identity, Metis Aboriginal rights would be too difficult to administer. More importantly, the Crown has argued that if Aboriginal rights are linked with pre-contact customs practices and traditions, the Metis could not possibly meet the Aboriginal rights test that has been established by the courts. But then came the decision in R. v. Powley making it clear that the Metis are a distinct people, separate from the Indians and the Inuit, with Aboriginal rights flowing from the customs, practices and traditions of Metis communities that emerged subsequent to the period of first contact, and prior to the exercise of "effective control" by the Crown. The Supreme Court of Canada found in favor of Powley by using a "purposive" approach in the analysis of Metis Aboriginal rights and by not mechanically applying the section 35 justification analysis. The purpose of this thesis is to develop a core set of principles that can be used as a framework for a purposive analysis of Metis Aboriginal rights. The principles support the propositions that: Metis fall within the exclusive legislative jurisdiction of the federal government; that Metis have Aboriginal rights that are recognized and affirmed by section 35; and, that Metis Aboriginal rights are immunized from the application of provincial wildlife regulations because of the doctrine of interjurisdictional immunity.